A transparent fluorescent ceramic with adjustable structure and its preparation method and application
By using the in-situ crystallization method of glass precursor heat treatment under normal pressure, excellent transparent blue fluorescent ceramics were prepared, which solved the problems of high cost and complex process of preparing transparent ceramic materials in the prior art, and achieved an efficient and low-cost preparation process, and had excellent optical properties and long afterglow luminescence characteristics.
Patent Information
- Application Number
- CN202410535977.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-29
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-04-29
AI Technical Summary
The prior art has problems such as high cost, complex process, vacuum or high pressure when preparing transparent ceramic materials, and insufficient transparency and mechanical strength of the prepared ceramics.
By using the in-situ crystallization method of glass precursor heat treatment under normal pressure, transparent fluorescent ceramics with a single MgAl2Si4O12:Eu2+, a single Mg2Al4Si5O18:Eu2+ crystal phase, and a dual crystal phase of MgAl2Si4O12:Eu2+ and Mg2Al4Si5O18:Eu2+ bicrystal phase were prepared.
It realizes a low-cost, simple process, and mass-produced transparent fluorescent ceramic. It has the characteristics of a compact glass/glass ceramic structure, excellent blue light luminous performance, quantum efficiency exceeds 88%, and has long afterglow luminous characteristics at high temperatures.
Smart Images

Figure CN118439860B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of luminescent materials, and in particular relates to a transparent fluorescent ceramic with adjustable structure, a preparation method and application thereof. Background Art
[0002] Ceramics is a typical multiphase system material, whose microstructure is almost entirely composed of nano- or micron-sized grains. The solid functional materials obtained by making ceramics transparent have many characteristics such as high mechanical strength, good heat resistance, and excellent optical properties. In recent years, transparent fluorescent ceramic materials have achieved extraordinary performance and effects in many fields such as solid lighting and display, laser, optical communication, X-ray imaging and infrared imaging. Therefore, in-depth research and development of high-performance transparent fluorescent ceramic materials is of great significance.
[0003] As is known to all, despite the great progress in ceramic technology, the preparation of transparent ceramics is still a difficult problem. Several known methods for preparing transparent ceramic materials have disadvantages such as high cost and complex process. In addition, most ceramic blanks require high purity raw materials, and are obtained by high-pressure molding of irregularly shaped powders. The ceramics prepared in this way will undoubtedly produce many pores, thereby reducing the transparency and mechanical strength of the ceramics. For example, CN101628811A discloses a method of cold isostatically pressing a blank into a vacuum sintering furnace to obtain Ln x Yb y Y (3-x-y) Al5O 12 , Ln w Yb z Y (2-w-z) Preparation method of O3 transparent ceramics. This method requires high purity of precursor raw materials, and the continuous vacuum environment during sintering leads to high cost and other disadvantages, which are difficult to be recognized by the market. CN106554192A discloses a preparation method of transparent ceramics obtained by grouting and hot isostatic pressing. Although this method has the advantage of mass production, it has the disadvantages of many production steps, long time consumption, complex process and high cost. CN112321295A discloses a method of synthesizing Y3Al5O by sol-gel method or liquid phase coprecipitation method 12 Preparation method of transparent ceramics. The ceramics prepared by this method have the characteristics of good optical uniformity and no stress, but the preparation is relatively complicated, the cost is high, and it cannot be mass-produced. CN113548883A uses a laser beam suspension melting method to prepare transparent ceramics. This method takes a short preparation time, and the prepared transparent ceramics have the characteristics of high density, but the disadvantage of extremely high cost has greatly hindered the widespread use of this method.
[0004] Therefore, there is an urgent need to provide a new method for preparing transparent ceramics, which does not require harsh conditions such as vacuum or high pressure, and the prepared transparent ceramics have good transparency and good optical properties. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a transparent fluorescent ceramic with adjustable structure and a preparation method and application thereof. The preparation method of the present invention uses the same precursor glass in-situ crystallization method to prepare a Eu doped 2+ The structure of rare earth ions is adjustable, transparent blue fluorescent ceramics. This method has low cost, simple process, and can be mass-produced. The prepared transparent fluorescent ceramics have the characteristics of compact glass / glass ceramic structure, that is, there are no light scattering sites (pores) to dissipate energy inside the material. More importantly, the same precursor glass can be obtained at different heat treatment temperatures: single MgAl2Si4O 12 :Eu 2+ Crystalline transparent fluorescent ceramics, single Mg2Al4Si5O 18 :Eu 2+ Crystalline transparent fluorescent ceramics, and MgAl2Si4O 12 :Eu 2+ 、Mg2Al4Si5O 18 :Eu 2+ Dual-phase transparent fluorescent ceramics. In particular, the single Mg2Al4Si5O 18 :Eu 2+ Crystalline transparent fluorescent ceramics (also known as Mg2Al4Si5O 18 :Eu 2+ Fully crystalline transparent fluorescent ceramics), good stability, good blue light emitting performance (quantum efficiency exceeds 88%, even reaching 90%), deep defect energy levels (for example, 0.73eV and 0.97eV respectively), good optical information storage capacity, etc., and long afterglow luminescence characteristics at high temperatures, and the afterglow lasts for tens of minutes.
[0006] A first aspect of the present invention provides a transparent fluorescent ceramic with adjustable structure.
[0007] Specifically, a structure-adjustable transparent fluorescent ceramic includes a single MgAl2Si4O 12 :Eu 2+ Crystal phase, single Mg2Al4Si5O 18 :Eu 2+ Crystalline phase, and MgAl2Si4O 12 :Eu 2+ and Mg2Al4Si5O 18 :Eu 2+ At least one of the twin phases.
[0008] Preferably, the transparent fluorescent ceramic has the characteristic of emitting blue light.
[0009] Preferably, the quantum efficiency of the transparent fluorescent ceramic exceeds 88%, for example, 89-92%.
[0010] Preferably, the defect energy level of the transparent fluorescent ceramic is 0.73-0.97 eV.
[0011] Preferably, the transparent fluorescent ceramic has no pores inside. That is, the transparent fluorescent ceramic has the characteristics of a compact glass / glass ceramic structure, that is, there are no light scattering sites (pores) to dissipate energy inside the material.
[0012] A second aspect of the present invention provides a method for preparing a transparent fluorescent ceramic with adjustable structure.
[0013] Specifically, a method for preparing a structure-adjustable transparent fluorescent ceramic comprises the following steps:
[0014] S1. Mixing silicon oxide, aluminum oxide, magnesium oxide and europium oxide to obtain a mixture;
[0015] S2, melting the mixture in step S1 in a reducing atmosphere, cooling, and obtaining a precursor amorphous glass;
[0016] S3, heat-treating the precursor amorphous glass in step S2 in a reducing atmosphere at a temperature of 800-1200° C. to obtain the transparent fluorescent ceramic.
[0017] In the present invention, if the heat treatment temperature in step S3 is lower than 800° C., a crystalline phase cannot be precipitated, and if the heat treatment temperature is too high, the glass will soften.
[0018] Preferably, in step S1, the silicon oxide includes at least one of SiO2 and SiO.
[0019] Preferably, in step S1, the aluminum oxide includes Al2O3.
[0020] Preferably, in step S1, the magnesium oxide includes MgO.
[0021] Preferably, in step S1, the europium oxide includes Eu2O3.
[0022] Preferably, in step S1, the mixture includes the following components in percentage by mass: SiO2 45%-75%, Al2O3 18%-32%, MgO 8%-22%, Eu2O3 0.01%-2.2%; further preferably, SiO2 50%-70%, Al2O3 20%-30%, MgO 10%-20%, Eu2O3 0.01%-2%.
[0023] Further preferably, the mixture includes the following components in percentage by weight: SiO2 60%, Al2O3 25.5%, MgO 14.49%, Eu2O3 0.01%. Under the conditions of the components, a single Mg2Al4Si5O 18 :Eu 2+ The crystalline phase has the best optical properties.
[0024] Preferably, in step S2, the reducing atmosphere is provided by H2, CO or carbon powder (such as activated carbon).
[0025] Preferably, in step S2, the melting temperature is 1300-1600°C, more preferably 1400-1600°C.
[0026] Preferably, in step S2, the melting time is 1-6 hours, more preferably 2-5 hours.
[0027] Preferably, in step S2, the cooling process is to directly take out at high temperature and cool to room temperature.
[0028] Preferably, in step S3, the temperature of the heat treatment is 1175-1200°C.
[0029] Preferably, in step S3, the reducing atmosphere is provided by H2, CO or carbon powder.
[0030] Preferably, in step S3, the heat treatment time is 20 min-16 h, more preferably 30-60 min.
[0031] Preferably, the preparation method comprises the following steps:
[0032] S1. Grind SiO2, Al2O3, MgO and Eu2O3 to obtain a mixed powder;
[0033] S2, placing the mixed powder described in step S1 in a reducing atmosphere at a temperature of 1400-1600° C. for melting for 1-6 hours, taking it out immediately after high-temperature melting and rapidly cooling it to obtain a precursor amorphous glass;
[0034] S3, subjecting the precursor amorphous glass of step S2 to heat treatment in a reducing atmosphere at a temperature of 800-1200° C., to obtain the transparent fluorescent ceramic material.
[0035] Preferably, in step S1, the grinding time is 20-30 min, for example, 20 min, 25 min, 30 min.
[0036] Preferably, in step S2, the mixed powder in step S1 is melted in a reducing atmosphere at a temperature of 1450-1500° C. for 3.5-4 hours.
[0037] A third aspect of the present invention provides an application of a transparent fluorescent ceramic with adjustable structure.
[0038] A device comprises the transparent fluorescent ceramic.
[0039] Preferably, the device comprises a lighting device or an optical storage device.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) The transparent fluorescent ceramic of the present invention comprises a single MgAl2Si4O 12 :Eu 2+ Crystal phase, single Mg2Al4Si5O 18 :Eu 2+ Crystalline phase, and MgAl2Si4O 12 :Eu 2+ and Mg2Al4Si5O 18 :Eu 2+ At least one of the twin phases. The transparent fluorescent ceramic has good stability, good blue light luminescence performance (quantum efficiency exceeds 88%, even up to 90%), has deep defect energy levels (for example, 0.73eV and 0.97eV respectively), has good optical information storage capacity and other advantages, and has long afterglow luminescence characteristics at high temperatures, and the afterglow duration is up to tens of minutes.
[0042] (2) The present invention utilizes an in-situ crystallization method of heat treating a glass precursor under normal pressure to efficiently and low-cost prepare blue light transparent fluorescent ceramics with excellent optical properties, wherein the same glass precursor is heat treated at different temperatures to obtain: a single MgAl2Si4O 12 :Eu 2+ Crystalline transparent fluorescent ceramics, single Mg2Al4Si5O 18 :Eu 2+ Crystalline transparent fluorescent ceramics, and MgAl2Si4O 12 :Eu 2+ and Mg2Al4Si5O 18:Eu 2+ Dual-phase transparent fluorescent ceramics, especially single Mg2Al4Si5O 18 :Eu 2+ Crystalline transparent fluorescent ceramics have the advantages of good blue light emitting performance (quantum efficiency reaches 90%), deeper defect energy levels (0.73eV and 0.97eV respectively), and better optical information storage capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The precursor glass of Example 1 of the present invention, the single MgAl2Si4O 12 :Eu 2+ Crystalline transparent fluorescent ceramics, single Mg2Al4Si5O 18 :Eu 2+ Crystalline transparent fluorescent ceramics, MgAl2Si4O 12 :Eu 2+ and Mg2Al4Si5O 18 :Eu 2+ XRD pattern of dual-phase transparent fluorescent ceramics;
[0044] Figure 2 It is MgAl2Si4O of Example 2 of the present invention 12 :Eu 2+ Visual diagram of transparent fluorescent ceramics;
[0045] Figure 3 The precursor glass and Mg2Al4Si5O 18 :Eu 2+ Visual diagram of transparent fluorescent ceramics;
[0046] Figure 4 The MgAl2Si4O obtained by heat treatment at 930°C for 16 hours in Example 2 of the present invention 12 :Eu 2+ Scanning electron microscope (SEM) image of transparent fluorescent ceramics;
[0047] Figure 5 The MgAl2Si4O obtained by heat treatment at 1100°C for 30 min in Example 3 of the present invention 12 :Eu 2+ and Mg2Al4Si5O 18 :Eu 2+ Scanning electron microscope (SEM) image of the dual-phase transparent fluorescent ceramic;
[0048] Figure 6 The Mg2Al4Si5O obtained by heat treatment at 1175°C for 30 min in Example 4 of the present invention 18 :Eu2+ Scanning electron microscope (SEM) image of transparent fluorescent ceramics;
[0049] Figure 7 It is MgAl2Si4O of Example 2 of the present invention 12 :Eu 2+ Excitation and emission spectra of transparent fluorescent ceramics;
[0050] Figure 8 It is MgAl2Si4O of Example 3 of the present invention 12 :Eu 2+ 、Mg2Al4Si5O 18 :Eu 2+ Excitation and emission spectra of dual-phase transparent fluorescent ceramics;
[0051] Fig. 9 It is Mg2Al4Si5O of Example 4 of the present invention 18 :Eu 2+ Excitation and emission spectra of transparent fluorescent ceramics;
[0052] Fig.10 It is Mg2Al4Si5O of Example 4 of the present invention 18 :Eu 2+ Quantum efficiency diagram of transparent fluorescent ceramics;
[0053] Fig.11 It is Mg2Al4Si5O of Example 4 of the present invention 18 :Eu 2+ Thermoluminescence spectrum of transparent fluorescent ceramics;
[0054] Fig.12 It is Mg2Al4Si5O of Example 4 of the present invention 18 :Eu 2+ Afterglow decay curves of transparent fluorescent ceramics at 300K and 660K respectively. DETAILED DESCRIPTION
[0055] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0056] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0057] Example 1
[0058] The preparation method of the precursor amorphous glass in this embodiment is as follows:
[0059] S1. Weigh the components according to the mass content of SiO2 60%, Al2O3 25.5%, MgO 14.49%, and Eu2O3 0.01%, mix and grind SiO2, Al2O3, MgO, and Eu2O3 for 30 minutes to obtain a mixed powder, and put it into a corundum crucible;
[0060] S2. Place the crucible containing the mixed powder in step S1 in a large crucible with a lid covered with activated carbon, keep it warm in a box furnace at 1500° C. for 4 hours to melt it, take it out immediately after melting, and cool it at room temperature to obtain a precursor amorphous glass.
[0061] The XRD spectrum of the precursor amorphous glass prepared in this embodiment is as follows: Figure 1 ( Figure 1 In the figure, "Intensity" means intensity, "degree" means degree) and "Glass" ("Glass" means precursor amorphous glass) are shown. Figure 1 The XRD pattern of the amorphous glass precursor of Example 1 shows no diffraction peaks, indicating that no crystals are precipitated in the glass, and the prepared glass is amorphous, and Figure 3 The figure "(A)" in the middle shows that the precursor amorphous glass with a thickness of 1.5 mm has a high transmittance, and the covered text can be clearly seen through the glass.
[0062] Example 2
[0063] This embodiment MgAl2Si4O 12 :Eu 2+ The preparation method of transparent fluorescent ceramics is as follows:
[0064] S1. Weigh the components according to the mass content of SiO2 60%, Al2O3 25.5%, MgO 14.49%, and Eu2O3 0.01%, mix and grind SiO2, Al2O3, MgO, and Eu2O3 for 30 minutes to obtain a mixed powder, and put it into a corundum crucible;
[0065] S2, placing the crucible containing the mixed powder in step S1 in a large crucible with a lid covered with activated carbon, keeping it warm for 4 hours in a box furnace at 1500° C. to melt it, taking it out immediately after melting, and cooling it at room temperature to obtain a precursor amorphous glass;
[0066] S3, heat-treating the precursor amorphous glass of step S2 in a reducing atmosphere (H2) at a temperature of 930°C for 16 hours to obtain MgAl2Si4O 12 :Eu 2+ Transparent fluorescent ceramic.
[0067] The XRD spectrum of the transparent fluorescent ceramic prepared in this embodiment is as follows: Figure 1 "930°C 16h" ("930°C 16h" corresponds to Example 2), Figure 1 The XRD diffraction peaks of the transparent fluorescent ceramics of Example 2 are consistent with those of the standard card PDF#27-0716 (MgAl2Si4O 12 :Eu 2+ ) one by one, and there is no amorphous diffraction hump corresponding to glass, and further combined with Figure 4 Scanning electron microscope (SEM) image ( Figure 4 It can be seen that the transparent fluorescent ceramic prepared in this embodiment has a grain size of about tens of microns and a very small grain boundary, indicating that MgAl2Si4O 12 :Eu 2+ Transparent fluorescent ceramics, and Figure 2 It is intuitively shown that the transparent fluorescent ceramic with a thickness of 1.5 mm in Example 2 exhibits good transparency. 12 :Eu 2+ Transparent fluorescent ceramics allow the covered text to be clearly seen.
[0068] pass Figure 7 ( Figure 7 "Wavelength" means wavelength, "Intensity" means intensity) of MgAl2Si4O 12 :Eu 2 + Excitation of transparent fluorescent ceramics ( Figure 7 Curve 1) and the emission spectrum ( Figure 7 From the curve 2), it can be seen that the transparent fluorescent ceramic of Example 2 can be effectively excited by the 230nm-430nm band, the emission spectrum range covers 375nm-750nm, and the emission peak is at 440nm in the blue light region.
[0069] Example 3
[0070] This embodiment MgAl2Si4O 12 :Eu 2+ and Mg2Al4Si5O 18 :Eu 2+ The preparation method of the double-crystal phase transparent fluorescent ceramic is as follows:
[0071] S1. Weigh the components according to the mass content of SiO2 60%, Al2O3 25.5%, MgO 14.49%, and Eu2O3 0.01%, mix and grind SiO2, Al2O3, MgO, and Eu2O3 for 30 minutes to obtain a mixed powder, and put it into a corundum crucible;
[0072] S2, placing the crucible containing the mixed powder in step S1 in a large crucible with a lid covered with activated carbon, keeping it warm for 4 hours in a box furnace at 1500° C. to melt it, taking it out immediately after melting, and cooling it at room temperature to obtain a precursor amorphous glass;
[0073] S3, heat-treating the precursor amorphous glass in step S2 in a reducing atmosphere (CO) at a temperature of 1100°C for 30 min to obtain MgAl2Si4O 12 :Eu 2+ and Mg2Al4Si5O 18 :Eu 2+ Dual-phase transparent fluorescent ceramics.
[0074] The XRD spectrum of the dual-phase transparent fluorescent ceramic prepared in this embodiment is as follows: Figure 1 "1100℃30min" shows ( Figure 1 "1100°C 30min" corresponds to Example 3), Figure 1 It shows that the dual-phase transparent fluorescent ceramic of Example 3 simultaneously precipitates MgAl2Si4O 12 :Eu 2+ (PDF#27-0716) and Mg2Al4Si5O 18 :Eu 2+ (PDF#84-1219) bicrystalline phase, in which there is no amorphous diffraction hump corresponding to glass, and Mg2Al4Si5O 18 :Eu 2+ The diffraction peak intensity of the crystal phase is greater than that of MgAl2Si4O 12 :Eu 2 + Crystal phase, indicating that in the double-phase transparent fluorescent ceramic of Example 3, Mg2Al4Si5O 18 :Eu 2+ The double-crystal phase transparent fluorescent ceramic prepared in Example 3 was further tested by scanning electron microscope. Figure 5 ( Figure 5 "ceramic" means ceramic) It can also be seen that it represents MgAl2Si4O 12 :Eu 2+ The rhombic grains of the crystal phase are randomly embedded in the Mg2Al4Si5O 18 :Eu 2+ In fluorescent ceramics dominated by the crystal phase.
[0075] pass Figure 8 ( Figure 8 "Wavelength" means wavelength, "Intensity" means intensity) of MgAl2Si4O 12 :Eu 2+ and Mg2Al4Si5O 18 :Eu 2+ Excitation of bicrystalline transparent fluorescent ceramics ( Figure 8 Curve 1) and emission ( Figure 8 From the spectrum of curve 2), it can be seen that the transparent fluorescent ceramic of Example 3 can be effectively excited by the 230nm-430nm band, the emission spectrum range covers 375nm-750nm, and the emission peak is at 458nm in the blue light region.
[0076] Example 4
[0077] In this embodiment, Mg2Al4Si5O 18 :Eu 2+ The preparation method of transparent fluorescent ceramics is as follows:
[0078] S1. Weigh the components according to the mass content of SiO2 60%, Al2O3 25.5%, MgO 14.49%, and Eu2O3 0.01%, mix and grind SiO2, Al2O3, MgO, and Eu2O3 for 30 minutes to obtain a mixed powder, and put it into a corundum crucible;
[0079] S2, placing the crucible containing the mixed powder in step S1 in a large crucible with a lid covered with activated carbon, keeping it warm for 4 hours in a box furnace at 1500° C. to melt it, taking it out immediately after melting, and cooling it at room temperature to obtain a precursor amorphous glass;
[0080] S3, heat-treating the precursor amorphous glass of step S2 in a reducing atmosphere (CO) at a temperature of 1175°C for 30 min to obtain Mg2Al4Si5O 18 :Eu 2+ Fully crystalline transparent ceramic.
[0081] The XRD spectrum of the fully crystalline transparent fluorescent ceramic prepared in this embodiment is as follows: Figure 1 As shown, Figure 1 It shows that the XRD diffraction peaks of the fully crystalline transparent ceramic of Example 4 are consistent with the standard card PDF#84-1219 (Mg2Al4Si5O 18 :Eu 2+ ) one by one, and there is no amorphous diffraction hump corresponding to glass, and further combined with Figure 6 ( Figure 6 The scanning electron microscope (SEM) image shows that the grains of the fully crystalline transparent fluorescent ceramic prepared in this embodiment are about tens of microns and the grain boundaries are very small, indicating that the Mg2Al4Si5O 18 :Eu 2+ Fully crystalline transparent ceramic.
[0082] Figure 3 The middle figure (B) intuitively shows that the fully crystalline transparent fluorescent ceramic with a thickness of 1 mm in Example 4 exhibits good transparency. 18 :Eu 2+ The fully crystalline transparent fluorescent ceramics allow the covered text to be clearly seen.
[0083] Fig. 9 ( Fig. 9 "Wavelength" means wavelength, "Intensity" means intensity) is Eu 2+ Mg2Al4Si5O with ion doping content of 0.1 (wt%) 18 :Eu 2+ Excitation of all-crystalline transparent fluorescent ceramics ( Fig. 9 Curve 1) and emission ( Fig. 9 Curve 2) in the spectrum diagram shows that the fully crystalline transparent fluorescent ceramic can be effectively excited at 220nm-440nm, the emission band covers 375nm-700nm, and the emission peak is located at 450nm in the blue light.
[0084] Fig.10 ( Fig.10 "Wavelength" means wavelength, "Intensity" means intensity) is Mg2Al4Si5O 18 :Eu 2+ Quantum efficiency (PLQY) of transparent fluorescent ceramics ( Fig.10 Curve 1 represents the blank control, and curve 2 represents Mg2Al4Si5O 18 :Eu 2+ The results show that the transparent fluorescent ceramic prepared in Example 4 has a quantum efficiency of up to 90%.
[0085] Fig.11 ( Fig.11 where "Temperature" indicates temperature and "TL intensity" indicates the luminous intensity at a specific temperature) is Mg2Al4Si5O 18 :Eu 2+ Thermoelectric spectrum of transparent fluorescent ceramics. The results show that the thermoelectric peak of the transparent fluorescent ceramic is wide and extends to a high temperature of 700K. Further calculations show that the trap depths of the transparent fluorescent ceramic are 0.73eV and 0.97eV, respectively, indicating that the transparent fluorescent ceramic has very deep defect energy levels and good defect energy level energy storage performance.
[0086] Fig.12 ( Fig.12"Time" means time, "Log intensity" means the logarithm of intensity, and "λ ex " indicates that the wavelength of the excitation light is 365 nm, and "Background" indicates the background) is Mg2Al4Si5O 18 :Eu 2+ The afterglow decay curves of the transparent fluorescent ceramics at 300K and 660K respectively show that the initial afterglow intensity of the transparent fluorescent ceramics at 660K is one order of magnitude higher than that at 300K, which is related to the accelerated release of trapped carriers. Moreover, with the increase of temperature, the afterglow performance shows a significant enhancement trend after 5 minutes, indicating that the transparent fluorescent ceramics are expected to be used in relevant high-temperature afterglow scenarios.
[0087] The present invention utilizes in-situ crystallization of a glass precursor by heat treatment under normal pressure to efficiently and low-cost prepare transparent blue light fluorescent ceramics with excellent optical properties, wherein the same glass precursor is heat treated at different temperatures to obtain: a single MgAl2Si4O 12 :Eu 2+ Crystalline transparent fluorescent ceramics, single Mg2Al4Si5O 18 :Eu 2+ Crystalline transparent fluorescent ceramics, and MgAl2Si4O 12 :Eu 2+ and Mg2Al4Si5O 18 :Eu 2+ Double-phase transparent fluorescent ceramics, including Mg2Al4Si5O 18 :Eu 2+ The fully crystalline transparent fluorescent ceramic has the advantages of good blue light emitting performance (quantum efficiency reaches 90%), deeper defect energy levels (0.73eV and 0.97eV respectively), and better optical information storage capacity.
[0088] In summary, the present invention uses the same precursor glass in-situ crystallization method to prepare a Eu-doped 2+ The structure of rare earth ions is adjustable, transparent blue light fluorescent ceramic material. This method has low cost, simple process, and can be mass-produced. The prepared ceramic has the characteristics of compact glass / glass ceramic structure, that is, there is no light scattering part (pore) to dissipate energy inside the material, and has good transparency. Importantly, the same precursor glass can be obtained at different heat treatment temperatures: single MgAl2Si4O 12 :Eu 2+ Crystalline transparent fluorescent ceramics, single Mg2Al4Si5O 18 :Eu 2+ Crystalline transparent fluorescent ceramics, and MgAl2Si4O 12 :Eu2+ and Mg2Al4Si5O 18 :Eu 2+ When the heat treatment temperature is within the range of the present invention, the prepared single MgAl2Si4O 12 :Eu 2+ Crystalline transparent fluorescent ceramics, single Mg2Al4Si5O 18 :Eu 2+ Crystalline transparent fluorescent ceramics, and MgAl2Si4O 12 :Eu 2+ and Mg2Al4Si5O 18 :Eu 2+ The double-phase transparent fluorescent ceramics can emit a broadband spectrum in the 375-700nm band under ultraviolet light excitation. More importantly, Mg2Al4Si5O 18 :Eu 2+ The fully crystalline transparent fluorescent ceramic has good thermal stability, highly efficient blue light emission (quantum efficiency reaches 90%) and good optical information storage capacity (with deeper defect energy levels of 0.73eV and 0.97eV respectively), and is expected to be used in fields such as high-power lighting and optical information storage.
[0089] Comparative Example 1
[0090] This comparative example Mg2Al4Si5O 18 :Mn 2+ The preparation method of transparent fluorescent ceramics is as follows:
[0091] S1. Weigh the components according to the mass content of SiO2 60%, Al2O3 25.5%, MgO 14.49%, and MnCO3 0.01%, mix and grind SiO2, Al2O3, MgO, and MnCO3 for 30 minutes to obtain a mixed powder, and put it into a corundum crucible;
[0092] S2, placing the crucible containing the mixed powder in step S1 in a large crucible with a lid covered with activated carbon, keeping it warm for 4 hours in a box furnace at 1500° C. to melt it, taking it out immediately after melting, and cooling it at room temperature to obtain a precursor amorphous glass;
[0093] S3, heat-treating the precursor amorphous glass of step S2 in a reducing atmosphere (H2) at a temperature of 1175°C for 30 min to obtain Mg2Al4Si5O 18 :Mn 2+ Fully crystalline transparent ceramic.
[0094] Mg2Al4Si5O in Comparative Example 1 18 :Mn 2+ Fully crystalline transparent ceramics do not emit light.
[0095] Comparative Example 2
[0096] This comparative example Mg2Al4Si5O 18 :Tb 3+ The preparation method of transparent fluorescent ceramics is as follows:
[0097] S1. Weigh the components according to the mass content of SiO2 60%, Al2O3 25.5%, MgO 14.49%, and Tb2O3 0.01%, mix and grind SiO2, Al2O3, MgO, and Tb2O3 for 30 minutes to obtain a mixed powder, and put it into a corundum crucible;
[0098] S2, placing the crucible containing the mixed powder in step S1 in a large crucible with a lid covered with activated carbon, keeping it warm for 4 hours in a box furnace at 1500° C. to melt it, taking it out immediately after melting, and cooling it at room temperature to obtain a precursor amorphous glass;
[0099] S3, heat-treating the precursor amorphous glass of step S2 in a reducing atmosphere (H2) at a temperature of 1175°C for 30 min to obtain Mg2Al4Si5O 18 :Tb 3+ Fully crystalline transparent ceramic.
[0100] Mg2Al4Si5O in Comparative Example 2 18 :Tb 2+ Fully crystalline transparent ceramics do not emit light.
[0101] Finally, it should be noted that the above embodiments are used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A transparent fluorescent ceramic, characterized in that: Including single MgAl2Si4O 12 :Eu 2+ Crystalline phase, and MgAl2Si4O 12 :Eu 2+ and Mg2Al4Si5O 18 :Eu 2+ At least one of the twin phases.
2. The transparent fluorescent ceramic according to claim 1, characterized in that: The transparent fluorescent ceramic has the characteristic of emitting blue light.
3. The transparent fluorescent ceramic according to claim 1, characterized in that: The quantum efficiency of the transparent fluorescent ceramic exceeds 88%.
4. The transparent fluorescent ceramic according to claim 1, characterized in that: The defect energy level of the transparent fluorescent ceramic is 0.73-0.97 eV.
5. The transparent fluorescent ceramic according to claim 1, characterized in that: The transparent fluorescent ceramic has no pores inside.
6. The method for preparing the transparent fluorescent ceramic according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Mixing silicon oxide, aluminum oxide, magnesium oxide and europium oxide to obtain a mixture; S2, melting the mixture in step S1 in a reducing atmosphere, cooling, and obtaining a precursor amorphous glass; S3, heat-treating the precursor amorphous glass in step S2 in a reducing atmosphere at a temperature of 800-1200° C. to obtain the transparent fluorescent ceramic.
7. The preparation method according to claim 6, characterized in that: In step S1, the silicon oxide includes at least one of SiO2 and SiO; and / or the aluminum oxide includes Al2O3; and / or the magnesium oxide includes MgO; and / or the europium oxide includes Eu2O3.
8. The preparation method according to claim 6, characterized in that: In step S1, the mixture includes the following components in percentage by mass: SiO2 45%-75%, Al2O3 18%-32%, MgO 8%-22%, Eu2O30.01%-2.2%; and / or, in step S2, the reducing atmosphere is provided by H2, CO or carbon powder; and / or, in step S2, the melting temperature is 1300-1600°C.
9. The preparation method according to claim 6, characterized in that: In step S3, the temperature of the heat treatment is 1175-1200°C; and / or, in step S3, the reducing atmosphere is provided by H2, CO or carbon powder; and / or, in step S3, the time of the heat treatment is 20min-16h.
10. A device, characterized in that: The transparent fluorescent ceramic comprises the transparent fluorescent ceramic according to any one of claims 1 to 5.
Citation Information
Patent Citations
Transparent ceramic and preparation method thereof
CN101628811A
Preparation method of transparent ceramic
CN106554192A
Preparation method of thulium-holmium double-doped yttrium aluminum garnet laser transparent ceramic
CN112321295A
Stable-output continuous white light transparent ceramic material and preparation method and application thereof
CN113548883A
Red-light-emitting glass ceramic and preparation method thereof, and LED / LD light emitting device
CN112194376A